The Influence of Western Culture on The Behavior of Z Generation - Sitti Rahmah; Virna Museliza; Ratna Nurani; Devi Deswimar (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This study aims to determine the influence of Western culture on the behavior of Generation Z in the city of Pekanbaru. And to find out that Western culture can influence the behavior of Generation Z in the city of Pekanbaru. The hypothesis was tested with a Simple Linear Regression Test, Partial Test Validity Test The results of his research based on statistical testers using the partial t test, showed that it had a t count value of 5.437> and T table 1.695 with a significance value of 0.000, namely (5.437> 1.695). So it can be concluded that Ho is rejected and Ha is accepted, meaning that Western Culture has a significant effect on Generation Z behavior in Pekanbaru city, meaning that if Western Culture advances, then Generation Za behavior will also change. Western Culture Variables have a positive and significant effect on the Behavior of Generation Z in the city of Pekanbaru with the appropriate significance value. There is a strong relationship between Western Culture on the Behavior of Generation Z in Pekanbaru City,